Estrategias metodológicas para mejorar los niveles de comprensión lectora: literal, inferencial y crítico, en los estudiantes de séptimo grado, en el área de Lengua y Literatura, bloque 2 “Leyendas Literarias”, de la escuela de educación básica José Ingenieros N° 2 del barrio Las Pitas, parroquia El Valle, cantón y provincia de Loja, en el periodo académico 2014-2015 - Quezada Pucha, Erika Alexandra (2015)
The research titled Methodological strategies to improve the reading comprehension levels: literal, inferential and critical of the students of seventh grade of the Department of Language and Literature, Block 2 "Literary Legends", José Ingenieros N° 2 School of Basic Education in Las Pitas neighborhood, El Valle Parish, Canton and Province of Loja, in the academic year 2014-2015, aimed at general objective: to apply methodological strategies to improve the reading comprehension levels: literal, inferential and critical of the students of seventh grade of the Department of Language and Literature, Block 2 "Literary Legends", José Ingenieros N° 2 School of Basic Education in the academic year 2014-2015, the research is a descriptive and quasi- experimental type, the following methods are used, scientific, comprehensive, analytical, synthetic, participatory diagnosis, proactive model, workshop and the comprehensive evaluation model as well as direct observation and the application of an interview techniques directed and the application of an interview aimed at the teacher and a survey for students. In the research work involved 21 human talents, a teacher and 20 students. At the end of the investigation it was concluded that there are problems in reading comprehension, students fail to interpret in your own words what they read and have low vocabulary, also the strategies used by the teacher are not enough to improve the improve reading comprehension, it is important that the teacher should include strategies in the process of reading as: finding the main idea make predictions, paraphrase, inferences, that allows to develop reading competition at the school